Philosophical and Foundational Issues in Measurement Theory - Savage, C.; Ehrlich, Philip (Psychology Press, 2013)
Measurement theory has only recently become recognized as a legitimate, specialized field of inquiry. This text covers a wide range of issues of central concern to contemporary measurement theorists, and a broad range of philosophical perspectives are represented. The formalist, representationalist approach defines measurement as the assignment of numbers to entities and events to represent their properties and relations. It also states that measurement theory is supposed to analyze the concept of a scale of measurement, describe various types of scales and their uses, and formulate the conditions required for the existence of scales of various types. Since this approach dominates contemporary measurement theory, the volume begins with essays by some of its leading architects. In order to allow for diverse points of view, the book also includes articles that attempt to broaden this approach, and several that even criticize the approach.